Sexual and mental health of Singaporean gay, bisexual and other men who have sex with men in times of COVID-19: a qualitative study - Xin Yi Seah; Rayner Kay Jin Tan; Xu Ming Yong; Miho Asano (International Journal of Qualitative Studies on Health & Well-Being)
Objectives COVID-19 had significant influences on everyone’s lives. This study aimed to explore impacts of COVID-19 on mental and sexual health and access to health services among gay, bisexual and other men who have sex with men (GBMSM) in Singapore. Methods This qualitative study recruited 16 self-identified GBMSM via purposive sampling and semi-structured individual interviews were conducted. Three themes and seven sub-themes were derived from analysis done using the framework method. Results Participants shared how COVID-19 led to negative emotions and experiences at an intrapersonal level and interpersonal level (with families or partners), which were also worsened by prevailing stigma that GBMSM already face in Singapore and within their social networks. Sexual behaviours associated with HIV and other sexually transmitted infections risk and substance use were seen to be maladaptive coping methods of social isolation due to COVID-19. These dynamics were all exacerbated by the closure of “non-essential” services, which included many important services for mental and sexual health that were relevant to the GBMSM community. Conclusions Changes in policies and community efforts should be explored to improve these areas, enhancing the psychosocial and sexual well-being of GBMSM.